The Fatality Risks of Sport-Utility Vehicles, Vans and Pickups - Ted Gayer (Economics and Econometrics Research Institute (EERI), 2001)
This paper presents a model of vehicle choice and empirically examines the risk posed by light trucks (sport-utility vehicles, vans, and pickups) to those that drive them and to other drivers, relative to the risk posed by cars. It compares the relative risk of dying and the relative crash frequencies of light trucks versus cars. The identification strategy uses information on pedestrian fatalities by vehicle type to correct for the sample selection bias that may exist due to the lack of reliable data on non-fatal crashes. Using data on all two-vehicle fatal crashes from 1991 through 1998, the results suggest that a light truck driver is 0.29 to 0.69 times as likely to die than is a car driver and is 1.48 to 2.63 times as likely to kill the opposing driver than is a car driver. Other data suggest that light trucks are approximately 2.2 times as likely to get into a crash than are cars.
Keywords: C20; D62; I18; R40; 330; Sample Selection Bias; Externalities; Public Health